2018
DOI: 10.3892/br.2018.1059
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of three-dimensional shear wave elastography in the detection of clinically significant prostate cancer

Abstract: Abstract. The present study evaluated three-dimensional shear wave elastography (3D SWE) in the detection of clinically significant prostate cancer. Clinically significant prostate cancer was defined by a minimum of one biopsy core with a Gleason score of 3+4 or 6 with a maximum cancer core length >4 mm. Patients with serum prostate-specific antigen levels of 4.0-20.0 ng/ml who were suspected of having prostate cancer from multi-parametric magnetic resonance imaging (mpMRI) were prospectively recruited. The 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In a clinical setting, the use of more planes per patient would reduce the risk of missing out-of-plane tumors at the cost of an increased procedure time. However, as 3D SWE and DCE-US have recently been introduced [55,56], expansion to three dimensions can be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, the use of more planes per patient would reduce the risk of missing out-of-plane tumors at the cost of an increased procedure time. However, as 3D SWE and DCE-US have recently been introduced [55,56], expansion to three dimensions can be envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the AUC of the scoring system based on SWE plus the clinical parameters (0.911) was significantly more diagnostically efficient than the scoring systems based on SWE alone (0.842) or clinical parameters alone (0.868). In addition, Shoji et al [29] indicated that combining Prostate Imaging Reporting and Data System Scores (PI-RADS) with measurement of Young's modulus by three-dimensional SWE improved the diagnosis of clinically significant prostate cancer. Moreover, Zhang et al [41] also demonstrated that multiparametric TRUS including greyscale imaging, colour Doppler imaging, SWE and contrast-enhanced ultrasound yielded a higher SEN, negative predictive value and accuracy than did multiparametric MRI (97.4% versus 94.7%, 96.9% versus 92.3% and 87.2% versus 76.9%, respectively) for detecting localized PCa.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 217 published studies were identified from the datasets in accordance with our search strategy. After removing the duplicates, screening the title and abstract and carrying out further evaluation, 13 studies were identified that use SWE for diagnosis of PCa; however, two studies provided insufficient data [28,29], one study was based on a total number of patients <20 [22] and one study enrolled patients with recurrent PCa [30]; hence, 9 studies were ultimately included in our present study [9,11,[31][32][33][34][35][36][37] (fig 1). Among the included studies, the study by Ahmad et al [9] was analysed twice according to PSA groupings of 4-20 ng/ml and over 20 ng/ml.…”
Section: Selected Studies and Quality Assessmentmentioning
confidence: 99%
“…The application of 3D shear wave elastography for clinical prostate cancer detection was proposed by Shoji et al 8 In their research, they used ultrasound pulse pressure to create shear waves in tissues, and they utilized this pulse as a means to measure tissue elasticity, which required trans-rectal guidance of the pulse to the prostate tissue. In this method, sensitivity, specificity, positive prediction, and negative prediction improved by 70%, 98%, 91%, and 92% in prostate tissue, respectively, and prostate lesions elasticity significantly correlated with Gleason score.…”
mentioning
confidence: 99%
“…In this method, sensitivity, specificity, positive prediction, and negative prediction improved by 70%, 98%, 91%, and 92% in prostate tissue, respectively, and prostate lesions elasticity significantly correlated with Gleason score. 8 Alizad et al and Mitri et al examined the application of vibro-acoustography in prostate tissue imaging and pointed out that the VA may use in clinical in-vivo prostate imaging. 9,10 There are also several neural simulations studies [11][12][13][14][15][16][17][18][19][20] ; however, artificial tactile sense and its applications widely used for mass detection.…”
mentioning
confidence: 99%